Application of ℓp norm regularisation techniques in the synthesis of indoor tyre pass-by noise with the inverse method. (12th May 2020) - Papaioannou, Athanasios; Elliott, Stephen J.; Cheer, Jordan
Abstract: Pass-by noise measurements can nowadays be realised in a laboratory environment with a microphone array and a stationary vehicle on a rolling road, according to ISO – 362–1:2016. Within this indoor testing procedure, the contributions from the various noise sources in a car can be estimated, with a set of microphones close to the various sources, and the pass-by noise then synthesised. The methods described in this paper use measured near field pressure data close to a rolling tyre at 50 km/h to estimate virtual source strength, using the inverse method, and the synthesised far field tyre noise is then compared with the one measured directly at a far field microphone array. A combination of ℓ 1 norm and ℓ 2 norm regularisation methods are investigated to optimise the equivalent source position and strength and, subsequently, the far field pass-by noise pressure estimates through the frequency range of interest. It is shown that by optimising the positions of 4 equivalent sources, acceptable representations of the measured far field spectra can be synthesised.